2020
DOI: 10.1158/2326-6066.cir-19-0568
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Fusion Burden as a Hallmark of Immune Infiltration in Prostate Cancer

Abstract: Prostate cancer is the second leading cause of cancer-associated death in men. Despite having a relatively lower tumor mutational burden than most tumor types, multiple gene fusions such as TMPRSS2:ERG have been characterized and linked to more aggressive disease. Individual tumor samples have been found to contain multiple fusions and it remains unknown whether these fusions increase tumor immunogenicity. Here, we investigated the role of fusion burden on the prevalence and expression of key molecular and imm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 30 publications
1
21
1
1
Order By: Relevance
“…Some series favored the fact that PD-L1 positivity may also be correlated to a more aggressive tumor stage and/or metastatic behavior. Except for one study (n = 171) [12], large cohorts showed that PD-L1 expression was higher in the advanced pT tumor stages (Xian et [28]) did not find any correlation. Calagua et al [75] also reported that patients with PD-L1+ PCs had higher serum PSA levels and rate of margin positivity on RP specimens.…”
Section: Discussionmentioning
confidence: 92%
“…Some series favored the fact that PD-L1 positivity may also be correlated to a more aggressive tumor stage and/or metastatic behavior. Except for one study (n = 171) [12], large cohorts showed that PD-L1 expression was higher in the advanced pT tumor stages (Xian et [28]) did not find any correlation. Calagua et al [75] also reported that patients with PD-L1+ PCs had higher serum PSA levels and rate of margin positivity on RP specimens.…”
Section: Discussionmentioning
confidence: 92%
“…Increased TRIM36 expression was associated with the inhibition of PC proliferation and cell-cycle progression through the inhibition of the MAPK/ERK pathway [123,184]. TRIM36 is also involved in antigen processing [32].…”
Section: Discussionmentioning
confidence: 99%
“…In another study [28], high tumor fusion burden (number of fusions/10,000 genes) correlated to high immune infiltration, PD-L1 expression on immune cells (negative on tumor cells), and immune signatures of T cells and M1 macrophages activation; conversely, it inversely correlated to immune suppressive signatures. Only late metastatic samples (n = 3) showed ≥10% of PD-L1 + inflammatory cells.…”
Section: Evaluation Of Pd-l1 Expression Density In Tumor Tissuementioning
confidence: 91%
“…In some studies, PD-L1 expression was significantly higher in PCs of all stages compared to benign prostatic hyperplasia or normal prostatic tissue (Wagle et al, p < 0.0001 [28]; Sharma et al, p < 0.001 [35]). Richter et al also found focal PD-L1 staining in <1% cells of a prostatic intraepithelial neoplasia [55].…”
Section: Pd-l1 Immunohistochemical Expression In Tumor Tissue: Benign Glands Vs Adenocarcinomamentioning
confidence: 95%
See 1 more Smart Citation